Peningkatan Kapasitas Dan Kualitas Pengolahan Produk Hasil Laut Di Surabaya Untuk Menembus Pasar Ekspor - Erna Ferrinadewi Kusnarsiyah (Universitas Negeri Surabaya, 2017)
In an effort to exploit Indonesia's rich marine potential of a variety of fish and given the large contribution of the growth of the fishery sector to Indonesia's gross domestic product, the seafood processing industry needs to improve the competitiveness of its products in order to increase the value of sea-based exports which in turn will improve the welfare of the community. SMEs engaged in the processing of seafood have not utilized science and technology in the production process so that found obstacles in the speed and fulfillment of export demand to neighboring countries. There are many work errors so shipping the product does not meet the standard of demand. The length of time the SMEs in fulfilling the buyer demand is caused by the length of the production process into the product ready to send. This work error results in the quality of the delivered product not meeting the health standards and the buyer's request. The ergonomic sorting table provides 2% reduction in work errors and the provision of wash tables designed to reduce work fatigue and the use of heating ovens to replace the sunlight function of the Cucumber products can increase the employee's working speed from 4 days to 2 days to prepare the product to send .